Proper Motion, Spectra, and Timing of Psr J1813-1749 Using Chandra and Nicer - Espinoza-Romo, C (Oxford University Press, 2020)
PSR J1813-1749 is one of the most energetic rotation-powered pulsars known, producing a pulsar wind nebula (PWN) and gamma-ray and TeV emission, but whose spin period is only measurable in X-ray. We present analysis of two Chandra data sets that are separated by more than 10 yr and recent NICER data. The long baseline of the Chandra data allows us to derive a pulsar proper motion μRA=(-0.067 ± 0.010) yr-1 and μDec.=(-0.014 ± 0.007) yr-1 and velocity v ≈ 900-1600 km, s-1 (assuming a distance d = 3-5 kpc), although we cannot exclude a contribution to the change in measured pulsar position due to a change in brightness structure of the PWN very near the pulsar. We model the PWN and pulsar spectra using an absorbed power law and obtain best-fitting absorption NH=(13.1 ± 0.9) × 1022 cm-2, photon index Γ = 1.5 ± 0.1, and 0.3-10 keV luminosity LX ≈ 5.4 × 1034, s-1(d/5 kpc)2 for the PWN and Γ = 1.2 ± 0.1 and LX ≈ 9.3 × 1033, s-1(d/5 kpc)2 for PSR J1813-1749. These values do not change between the 2006 and 2016 observations. We use NICER observations from 2019 to obtain a timing model of PSR J1813-1749, with spin frequency ν = 22.35 Hz and spin frequency time derivative nu=(-6.428 ± 0.003) × 10-11Hz, s-1. We also fit ν measurements from 2009 to 2012 and our 2019 value and find a long-term spin-down rate nu=(-6.3445 ± 0.0004) × 10-11Hz, s-1. We speculate that the difference in spin-down rates is due to glitch activity or emission mode switching. © 2020 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.